Vasily Vasilyevich Davydov in Nizhnevartovsk: Expanding the Educational Space of Developmental Learning - Maximov L.K; Maximova L.V (Moscow State University of Psychology and Education, 2020)
Using one of the Russian regions as an example, the article describes the activities of an outstanding Russian psychologist and scientist V.V. Davydov during the period of active introduction of the technology of learning activity into the mass educational practice in Russian schools. We outline the problems V.V. Davydov was interested in, the ones connected with the practical implementation of the theoretical approach of his scientific school to the development of a new content, forms and methods of education. The applied researches of V.V. Davydov's scientific school which were defined as the system of developmental learning by D.B. Elkonin-V.V. Davydov are still in demand. We describe the attitude of V.V. Davydov to the regional specifics of training teachers for the Elkonin- Davydov developmental learning system and to teaching primary school children with special educational needs within the learning activity framework. The article is based on our recollections, audio and video recordings of V.V. Davydov at a scientific and practical seminar, meetings with teachers and students of Nizhnevartovsk and Megion.